STRATEGI UNIT BISNIS DALAM INOVASI PRODUK DAN LAYANAN DI PERBANKAN SYARIAH - Adhe Pertiwi Mareta; Abib Novriyanto; Heni Noviarita (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2026)
This article aims to analyze the role of business unit strategies in product and service innovation in Islamic banking. This study uses library research methods by examining various sources such as scientific journals, books, and official reports related to business strategy and innovation in the context of the Islamic economy. The results show that Islamic business unit strategies serve as a roadmap for achieving competitive advantage, as well as a foundation for ensuring that every innovation process remains based on Islamic principles. An effective strategy must be able to integrate Islamic value orientation, business environment analysis, internal resource management, and digital transformation. Product and service innovations, such as Islamic fintech, blockchain, and Islamic crowdfunding, are concrete evidence of the application of these strategies in responding to technological changes and the needs of modern customers. The relationship between business unit strategy and innovation is reciprocal: strategy provides direction for innovation, while innovation becomes a means of actualizing strategy in Islamic banking practice. Thus, strengthening business unit strategies based on digitalization and Islamic values is key to the sustainability and competitiveness of Islamic banking in the modern era.